High specific energy-multiplying power type cobalt-based metal organic framework negative electrode material, preparation method and application

By preparing Co-NTTA MOFs anode material with a sp2 hybrid carbon structure with π-aromatic conjugated network and π...π stacked sp2 hybrid carbon structure, the problem of volume effect and dynamic growth of SEI film in the lithiation/delithation process of lithium-ion battery anode material is solved, and high specific capacity and excellent rate performance are achieved.

CN119505264AActive Publication Date: 2025-02-25SOUTHWEST JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411615837.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-25
Estimated Expiration
2044-11-13

AI Technical Summary

Technical Problem

The existing lithium-ion battery anode materials have volume effects and dynamic growth of SEI films during the lithiation/delithation process, resulting in rapid attenuation of battery capacity and shortening of cycle life, making it difficult to achieve rapid charging and discharge.

Method used

Using triphenylamine triamide-derived hexacarboxylic acid as the organic ligand, cobalt nitrate hexahydrate as the metal center source, Co-NTTA MOFs anode material with a π-aromatic conjugated network and π...π stacked sp2 hybrid carbon structure was prepared by solvothermal reaction.

Benefits of technology

High specific capacity and excellent rate performance are achieved. The assembled Co-NTTA MOF||Li lithium-ion battery has a capacity output of up to 956mAhg-1 at a current density of 200mAg-1, and the discharge capacity is maintained at 483mAhg-1 after cycling for 600 cycles at a high current density of 5Ag-1, showing excellent electrochemical stability and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505264A_ABST
    Figure CN119505264A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of preparation of lithium ion battery negative electrode new materials, and particularly relates to a high specific energy-multiplying power type cobalt-based metal organic framework negative electrode material, a preparation method and application. The preparation method specifically comprises the following steps: S1, mixing a triphenylamine triamide derived hexacarboxylic acid organic ligand (H6NTTA, C45H30N4O15), cobalt nitrate hexahydrate metal salt (Co (NO3) 2.6 H2O), N, N-diethylformamide (DMF) and ethanol, adding the mixture into a reaction kettle, sealing, putting into a constant-temperature oven for reaction, and after the reaction is finished, cooling to room temperature to obtain a cobalt-based metal organic framework material (Co-NTTA MOFs); and S2, mixing the Co-NTTA MOFs obtained in the step S1 with conductive carbon black, a binder and a solvent to obtain a mixture, defoaming and stirring to obtain uniform slurry, drying the uniform slurry at a constant temperature in vacuum, and cutting to obtain the cobalt-based metal organic framework negative electrode. The preparation method is simple in preparation process and simple in process, and is beneficial to directly forming a process production line for efficient production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of preparation of new negative electrode materials for lithium-ion batteries, and in particular relates to a high specific energy-rate cobalt-based metal organic framework negative electrode material, a preparation method and an application thereof. Background Art

[0002] With the booming development of portable electronic devices, electric vehicles, aviation equipment and smart grids, traditional chemical power sources represented by lithium-ion batteries can no longer meet the urgent needs of national strategies and consumers for long battery life, fast charging and other characteristics. Therefore, it is urgent to develop high-energy-density and rate-type energy storage technologies that surpass traditional electrochemical energy sources. Graphite, as the most mature negative electrode material currently used in lithium-ion batteries, has the advantages of stable structure, low lithium insertion potential, long cycle life, high conductivity and low cost. However, the theoretical specific capacity of graphite negative electrode is low (372mAhg -1 ) and in practical applications, they face problems such as the continuous growth of the surface solid electrolyte interface (SEI) film and difficulty in achieving fast charging. In recent years, transition metal oxides, sulfides, nitrides, and high-capacity inorganic negative electrode materials such as silicon, germanium, and tin alloys have gradually become ideal candidates to replace graphite. They have received widespread attention from the scientific research community and the battery industry, and have been initially applied. However, during the lithiation / delithiation process, such inorganic negative electrode materials often experience a drastic volume effect, resulting in mechanical crushing of the battery materials, and the SEI film on the electrode surface will grow dynamically, ultimately leading to rapid attenuation of the battery capacity and shortened cycle life, restricting its practical application. In addition, in addition to performance bottlenecks, issues such as resource reserves, synthesis energy consumption, and the difficulty of battery recycling also need to be given priority attention when developing inorganic negative electrode materials.

[0003] Organic materials have attracted much attention as electrode materials in recent years due to their advantages such as green environmental protection, strong molecular structure designability and adjustable redox potential. However, organic electrode materials are easy to dissolve and shuttle and have strong electrical insulation. These problems seriously restrict their potential to achieve high reversible capacity and excellent rate performance at the same time. Therefore, exploring negative electrode materials with stable structure and superior electrochemical performance has become an important research direction for the development of new generation lithium-ion batteries. Metal-organic frameworks (MOFs) are a class of crystalline porous materials formed by self-assembly of organic ligands and inorganic metal ions or metal clusters through coordination bond bridging. Due to their advantages such as high specific surface area, rich pore structure and easy functionalization, they have been widely used in gas storage and separation, heterogeneous catalysis, sensing, drug delivery and nonlinear optics. In recent years, metal-organic framework materials have also shown great application potential in the field of electrochemical energy storage and have been proven to be directly used as negative electrode materials for lithium-ion batteries. It achieves efficient lithium storage through the functional groups on the organic ligands and the multiple active sites of the metal center, and its excellent structural stability can effectively solve the dissolution and shuttle problem of organic electrode materials, thereby achieving high capacity output and long cycle stability. However, the current rate performance of metal organic frameworks as negative electrode materials for lithium-ion batteries still needs to be further improved to meet the needs of fast charging and discharging. Therefore, it is urgent to design and develop sp-based materials with π-aromatic conjugated networks and π...π stacking. 2 Hybrid carbon structured metal organic framework anode materials. By enhancing electron delocalization, reducing the band gap and improving electronic conductivity, more efficient, fast and stable lithium storage behavior can be achieved. Summary of the invention

[0004] In view of the above defects or improvement needs of the prior art, the present invention aims to provide a high specific energy-rate type cobalt-based metal organic framework negative electrode material, a preparation method and application thereof, wherein the preparation method comprises the following steps:

[0005] S1: triphenylamine triamide-derived hexacarboxylic acid organic ligand, Co(NO3)2·6H2O, N,N-diethylformamide and ethanol are mixed and added into a reaction kettle, which is sealed and placed in a constant temperature oven for reaction. After the reaction is completed, the mixture is cooled to room temperature to obtain Co-NTTA MOFs;

[0006] S2: The Co-NTTA MOFs obtained in S1 are mixed with conductive carbon black, a binder and a solvent to obtain a mixture, and a uniform slurry is obtained by degassing and stirring. The slurry is dried at a constant temperature under vacuum, and a cobalt-based metal organic framework negative electrode is obtained by cutting.

[0007] Furthermore, the reaction time described in S1 is 3 days, and the reaction kettle is 25 mL.

[0008] Furthermore, the volume ratio of N,N-diethylformamide to ethanol described in S1 is 2-6:1-3.

[0009] A high specific energy-rate cobalt-based metal organic framework negative electrode material, the negative electrode material is a sp with abundant lithium storage sites, excellent structural stability, π-aromatic conjugated network and π...π stacking 2 Hybridized carbon structure.

[0010] The invention discloses an application of a high specific energy-rate type cobalt-based metal organic framework negative electrode material, wherein the cobalt-based metal organic framework negative electrode material is applied in assembling lithium ion batteries and hybrid ion capacitors.

[0011] Beneficial Effects

[0012] (1) According to the preparation method of a high specific energy-rate cobalt-based metal organic framework negative electrode material provided by the present invention, triphenylamine triamide-derived hexacarboxylic acid (H6NTTA) is used as an organic ligand, and cobalt nitrate hexahydrate (Co(NO3)2·6H2O) is used as a metal center source, and a three-dimensional cobalt-based metal organic framework (Co-NTTA MOFs) material is prepared by solvent thermal reaction. The preparation process is concise, the process is simple, and the experimental repeatability is good, which is conducive to directly forming a process production line for efficient production.

[0013] (2) Through the high specific energy-rate cobalt-based metal organic framework negative electrode material provided by the present invention, the novel Co-NTTA MOFs prepared by the present invention have abundant lithium storage sites (-OC=O, -NH-C=O, active -C=C functional groups and cobalt cations), excellent structural stability, π-aromatic conjugated network and π...π stacked sp 2 Hybridized carbon.

[0014] (3) Through the application of a high specific energy-rate type cobalt-based metal organic framework negative electrode material provided by the present invention, the invention directly uses Co-NTTAMOFs with a novel structure as a negative electrode material for lithium-ion batteries. The assembled Co-NTTA MOF||Li lithium-ion battery has a current density of 200mAg -1 The capacity output is up to 956mAhg -1 ; and in 5Ag -1 At high current density, the discharge capacity remains at 483 mAh g after 600 cycles. -1 , showing excellent electrochemical stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following is a brief introduction to the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:

[0016] Figure 1 This is a schematic diagram of the synthesis process of the high specific energy-rate type cobalt-based metal organic framework negative electrode material prepared in Example 1 of the present invention;

[0017] Figure 2 This is an attenuated total reflection Fourier transform infrared (ATR-FTIR) spectrum of the high specific energy-rate type cobalt-based metal organic framework anode material prepared in Example 1 of the present invention;

[0018] Figure 3 The powder X-ray diffraction (PXRD) pattern of the high specific energy-rate type cobalt-based metal organic framework negative electrode material prepared in Example 1 of the present invention;

[0019] Figure 4 The scanning electron microscope image and morphology schematic diagram of the high specific energy-rate cobalt-based metal organic framework negative electrode material prepared in Example 1 of the present invention;

[0020] Figure 5 The HAADF-STEM image, selected area electron diffraction image and corresponding element distribution image of the high specific energy-rate cobalt-based metal organic framework negative electrode material prepared in Example 1 of the present invention;

[0021] Figure 6 This is a rate performance diagram of a high specific energy-rate cobalt-based metal organic framework negative electrode assembled Co-NTTAMOF||Li lithium-ion battery prepared in Example 1 of the present invention;

[0022] Figure 7 This is a comparison chart of the rate performance of the high specific energy-rate type cobalt-based metal organic framework anode prepared in Example 1 of the present invention and the anode material based on the organic framework reported in the literature for advanced lithium-ion batteries;

[0023] Figure 8 The electrochemical impedance spectra of the high specific energy-rate cobalt-based metal organic framework negative electrode prepared in Example 1 of the present invention at different cycle periods;

[0024] Fig. 9 The high specific energy-rate cobalt-based metal organic framework negative electrode assembled Co-NTTAMOF||Li lithium-ion battery prepared in Example 1 of the present invention is 1 and 5Ag -1 Long cycle curves and Coulomb efficiency diagrams at different current densities;

[0025] Fig.10 The high specific energy-rate cobalt-based metal organic framework negative electrode assembled Co-NTTAMOF||Li lithium-ion battery prepared in Example 1 of the present invention is 1 and 5Ag -1 The charge and discharge curves of different cycle numbers under current density;

[0026] Fig.11 This is a comparison chart of the long cycle performance of the high specific energy-rate type cobalt-based metal organic framework anode prepared in Example 1 of the present invention and the anode material based on the organic framework reported in the literature for advanced lithium-ion batteries;

[0027] Fig.12 The rate performance diagram of the Co-NTTA MOF||AC lithium-ion hybrid capacitor constructed with different mass ratios of the high specific energy-rate cobalt-based metal organic framework negative electrode and the activated carbon positive electrode prepared in Example 1 of the present invention;

[0028] Fig.13 This is a comparison chart of the electrochemical performance of the high specific energy-rate cobalt-based metal organic framework anode prepared in Example 1 of the present invention and the organic framework-based anode material reported in the literature for advanced Co-NTTA MOF||AC lithium ion hybrid capacitors;

[0029] Fig.14 The Co-NTTA MOF||AC lithium-ion hybrid capacitor constructed by the high specific energy-rate type cobalt-based metal organic framework negative electrode and activated carbon positive electrode prepared in Example 1 of the present invention is 5Ag -1 Long cycle curve under current density and charge and discharge curves of different cycle numbers. DETAILED DESCRIPTION

[0030] The following will be combined with Embodiments 1 to 6 of the present invention and the attached Figures 1 to 14 , the technical solution of the present invention is clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The preparation method provided by the present invention provides a sp-type lithium-ion battery having abundant lithium storage sites (-OC=O, -NH-C=O, active -C=C functional groups and cobalt cations), excellent structural stability, π-aromatic conjugated network and π...π stacking. 2 A novel Co-NTTA MOFs based on hybrid carbon. The material is prepared by deriving hexacarboxylic acid (H6NTTA, C 45 H 30 N4O 15) as an organic ligand and cobalt nitrate hexahydrate (Co(NO3)2·6H2O) as a metal center source, a three-dimensional cobalt-based metal organic framework (Co-NTTA MOFs, Co7C 90 N8O 62.50 H 111 ). Co-NTTAMOFs were directly used as negative electrode materials for lithium-ion batteries. The assembled Co-NTTA MOF||Li lithium-ion battery exhibited a high specific capacity (956 mAh g -1 , 200mAg -1 ) and excellent rate performance (483mAhg -1 , 600 th , 5Ag -1 Based on the Faradaic redox reaction of Co-NTTA MOFs and the fast intercalation pseudocapacitive lithium storage mechanism, a 4.3V high-performance lithium-ion hybrid capacitor was successfully constructed.

[0032] The present invention provides a method for preparing a high specific energy-rate cobalt-based metal organic framework negative electrode material, comprising the following steps:

[0033] S1: First, add triphenylamine triamide-derived hexacarboxylic acid organic ligand, metal salt Co(NO3)2·6H2O, N,N-diethylformamide (DMF) and ethanol into the reactor, seal it and place it in a constant temperature oven for three days; after the reaction, cool it to room temperature to finally obtain light purple cubic block crystals Co-NTTA MOFs. S2: Mix the light purple powder Co-NTTAMOFs, conductive carbon black and binder obtained in S1 in a certain mass ratio, add solvent, and stir with a THINKY degassing machine to make a slurry; evenly scrape the obtained black viscous slurry on one side of the copper foil current collector and dry it at a constant temperature under vacuum; use a cutting machine to punch out a circular electrode with a diameter of 11 mm. The active mass of a single lithium-ion battery negative electrode is 1.5-2.0 mgcm -2 , and obtained a cobalt-based metal organic framework anode (Co-NTTA MOFs electrode sheet).

[0034] Example 1

[0035] S1: Triphenylamine triamide derivative hexacarboxylic acid (C 45 H 30 N4O 15, 17 mg, 0.02 mmol) organic ligand, metal salt Co(NO3)2·6H2O (29.1 mg, 0.1 mmol), N,N-diethylformamide (DMF, 4 mL) and ethanol (2 mL) were added into a 25 mL reactor, which was sealed and placed in a 100 °C constant temperature oven for three days. After the reaction was completed, it was cooled to room temperature to finally obtain light purple cubic block crystals of Co-NTTA MOFs.

[0036] The Co-NTTA MOFs obtained in S1 were mixed with super P and PVDF in a mass ratio of 6:3:1, and N-methylpyrrolidone (NMP) solvent was added. The mixture was stirred for 30 min using a THINKY degassing machine to prepare a slurry. The obtained black viscous slurry was evenly scraped onto one side of the copper foil current collector and dried at a constant temperature of 120 °C for 12 h under vacuum conditions. A circular electrode with a diameter of 11 mm was punched out using a cutting machine. The active mass of a single lithium-ion battery negative electrode was 1.5 mg cm -2 , and a cobalt-based metal organic framework negative electrode was obtained. A lithium sheet was used as a reference electrode and a counter electrode, a Celgard 2400 membrane was used as a separator, and a 1M lithium hexafluorophosphate-ethylene carbonate / diethyl carbonate (1:1, volume ratio) electrolyte was used. The prepared Co-NTTA MOFs electrode sheet was used as a negative electrode to assemble a Co-NTTA MOF||Li lithium-ion battery.

[0037] To reduce polarization and improve coulombic efficiency, Co-NTTA MOFs anode was used in lithium-ion batteries at 50 mA g -1 The current density was pre-cycled until the coulombic efficiency exceeded 95%. Then, the battery was discharged to 0.01 V (vs. Li / Li + ) and then assemble the full battery. Pre-lithiated Co-NTTA MOFs were used as the negative electrode and activated carbon as the positive electrode to construct a lithium-ion hybrid capacitor. Activated carbon, conductive carbon black and binder were mixed evenly in a mass ratio of 9:0.5:0.5, a solvent was added, and stirred in a THINKY degassing machine for 30 minutes to make a slurry. The resulting black viscous slurry was evenly scraped and applied to one side of the aluminum foil current collector and dried at a constant temperature of 120°C under vacuum conditions for 12 hours. The optimal electrochemical performance of the lithium-ion hybrid capacitor was achieved by optimizing the mass ratio of active materials between the Co-NTTA MOFs negative electrode and the activated carbon positive electrode to 1:7. The total mass of Co-NTTA MOFs and activated carbon was controlled at 16 mg / cm -2 .

[0038] Combination Figure 1The synthesis route and molecular structure schematic diagram of Co-NTTA MOFs can be seen, in which H6NTTA organic ligand and Co(NO3)2·6H2O are uniformly dispersed in a mixed solvent containing N,N-diethylformamide and ethanol, and a simple wet chemical reaction is used to promote uniform crystallization to generate a light purple powder, that is, the Co-NTTA MOFs product is obtained.

[0039] Combination Figure 2 It can be seen that the chemical structure of Co-NTTA MOFs was confirmed by attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR), which confirmed the successful coordination polymerization between H6NTTA organic ligands and cobalt cations.

[0040] Combination Figure 3 It can be seen that the powder X-ray diffraction (PXRD) spectrum of Co-NTTA MOFs is highly consistent with the single crystal data simulation spectrum, confirming its phase purity and high crystallinity.

[0041] Combination Figure 4 It can be seen that Co-NTTA MOFs have a regular shape and a large crystal size. They are standard cubes with smooth surfaces and an average side length of 20 to 30 μm.

[0042] Combination Figure 5 It can be seen that the energy dispersive X-ray (EDS) element distribution images confirm that Co, C, O and N elements are uniformly distributed in Co-NTTAMOFs.

[0043] Combination Figure 6 It can be seen that Co-NTTA||Li lithium-ion battery has a high -1 It exhibits excellent rate performance at low current density.

[0044] Combination Figure 7 It can be seen that the rate performance of Co-NTTA||Li lithium-ion batteries far exceeds the rate characteristics of almost all previously reported organic framework-based negative electrode materials, indicating that Co-NTTAMOFs negative electrode materials exhibit ultrafast lithium storage kinetics.

[0045] Combination Figure 8 It can be seen that the Nyquist plots of Co-NTTA||Li lithium-ion batteries at different cycle numbers indicate excellent interfacial stability and fast electrochemical response.

[0046] Combination Fig. 9 It can be seen that Co-NTTA||Li lithium-ion batteries have a high -1 It exhibits excellent long-cycle stability and high Coulombic efficiency at low current density.

[0047] Combination Fig.10It can be seen that Co-NTTA||Li lithium-ion battery at 1Ag -1 The charge and discharge curves at different current densities are highly overlapped, indicating high reversibility, and the coulombic efficiency exceeds 99.8%.

[0048] Combination Fig.11 It can be seen that the long-cycle performance of Co-NTTA||Li lithium-ion batteries is particularly outstanding among the long-cycle characteristics of a series of organic framework-based negative electrode materials reported so far, further emphasizing its potential in practical applications.

[0049] Combination Fig.12 It can be seen that the optimal mass ratio of Co-NTTA negative electrode to AC positive electrode in the Co-NTTA||AC lithium-ion hybrid capacitor is 1:7, and it exhibits excellent rate performance.

[0050] Combination Fig.13 It can be seen that the energy density and power density output by Co-NTTA||AC lithium-ion hybrid capacitors are significantly superior to the electrochemical performance of recently reported advanced organic framework-based lithium-ion hybrid capacitors.

[0051] Combination Fig.14 It can be seen that Co-NTTA||AC lithium-ion hybrid capacitors have a high -1 After 10,000 cycles at the current density, the average capacity decay rate per cycle is as low as 0.00024%, showing an extremely long service life.

[0052] Example 2

[0053] S1: Add triphenylamine triamide-derived hexacarboxylic acid (17 mg, 0.02 mmol) organic ligand, metal salt Co(NO3)2·6H2O (29.1 mg, 0.1 mmol), N,N-diethylformamide (DMF, 2 mL) and ethanol (2 mL) into a 25 mL reactor, seal it and place it in a 100 °C constant temperature oven for three days; after the reaction is completed, cool it to room temperature to finally obtain light purple cubic block crystals Co-NTTA MOFs.

[0054] The Co-NTTA MOFs, KB and PTFE obtained in S1 were mixed evenly in a mass ratio of 5:4:1, deionized water / ethanol solvent was added, and the mixture was stirred for 30 min using a THINKY degassing machine to prepare a slurry. The obtained black viscous slurry was evenly scraped onto one side of the copper foil current collector, dried at a constant temperature of 120 °C for 12 h under vacuum conditions, and a circular electrode with a diameter of 11 mm was punched out using a cutting machine. The active mass of a single lithium-ion battery negative electrode sheet is 2.0 mg cm -2, a cobalt-based metal organic framework anode was obtained; a lithium sheet was used as a reference electrode and a counter electrode, a Celgard 2400 membrane was used as a separator, and a 1M lithium bis(trifluoromethylsulfonyl)imide-ethylene carbonate / diethyl carbonate (1:1, volume ratio) electrolyte was used. The prepared Co-NTTAMOFs electrode sheet was used as a cathode to assemble a Co-NTTA MOF||Li lithium-ion battery.

[0055] To reduce polarization and improve coulombic efficiency, Co-NTTA MOFs anode was used in lithium-ion batteries at 50 mA g -1 The battery was pre-cycled at a current density of 100 μm until the coulombic efficiency exceeded 95%. The battery was then discharged to 0.01 V (vs. Li / Li + ) and then assemble the full battery. Pre-lithiated Co-NTTA MOFs were used as the negative electrode and activated carbon as the positive electrode to construct a lithium-ion hybrid capacitor. Activated carbon, conductive carbon black and binder were mixed evenly in a mass ratio of 8:1:1, a solvent was added, and stirred in a THINKY degassing machine for 30 minutes to make a slurry; the resulting black viscous slurry was evenly scraped on one side of the aluminum foil current collector and dried at a constant temperature of 120°C under vacuum conditions for 12 hours; the optimal electrochemical performance of the lithium-ion hybrid capacitor was achieved by optimizing the active material mass ratio between the Co-NTTA MOFs negative electrode and the activated carbon positive electrode to 1:4. The total mass of Co-NTTA MOFs and activated carbon was controlled at 13 mg / cm -2 .

[0056] Example 3

[0057] S1: Add triphenylamine triamide-derived hexacarboxylic acid (17 mg, 0.02 mmol) organic ligand, metal salt Co(NO3)2·6H2O (29.1 mg, 0.1 mmol), N,N-diethylformamide (DMF, 6 mL) and ethanol (1 mL) into a 25 mL reactor, seal it and place it in a 100 °C constant temperature oven for three days; after the reaction is completed, cool it to room temperature to finally obtain light purple cubic block crystals Co-NTTA MOFs.

[0058] The Co-NTTA MOFs, carbon nanotubes and acrylonitrile multipolymer dispersion obtained in S1 were mixed evenly in a mass ratio of 8:1:1, deionized water solvent was added, and the mixture was stirred for 30 min using a THINKY degassing machine to prepare a slurry. The obtained black viscous slurry was evenly scraped onto one side of the copper foil current collector and dried at a constant temperature of 120 °C for 12 h under vacuum conditions. A circular electrode with a diameter of 11 mm was punched out using a cutting machine. The active mass of a single lithium-ion battery negative electrode was 2.0 mg cm -2, a cobalt-based metal organic framework anode was obtained; a lithium sheet was used as a reference electrode and a counter electrode, a Celgard 2400 membrane was used as a separator, and a 1M lithium perchlorate-ethylene carbonate / diethyl carbonate (1:1, volume ratio) electrolyte was used. The prepared Co-NTTA MOFs electrode sheet was used as a cathode to assemble a Co-NTTA MOF||Li lithium-ion battery.

[0059] To reduce polarization and improve coulombic efficiency, Co-NTTA MOFs anode was used in lithium-ion batteries at 50 mA g -1 The current density was pre-cycled until the coulombic efficiency exceeded 95%. Then, the battery was discharged to 0.01 V (vs. Li / Li + ) and then assemble the full battery. Pre-lithiated Co-NTTA MOFs were used as the negative electrode and activated carbon as the positive electrode to construct a lithium-ion hybrid capacitor. Activated carbon, conductive carbon black and binder were mixed evenly in a mass ratio of 7:2:1, a solvent was added, and stirred in a THINKY degassing machine for 30 minutes to make a slurry. The resulting black viscous slurry was evenly scraped on one side of the aluminum foil current collector and dried at a constant temperature of 120°C under vacuum conditions for 12 hours. The optimal electrochemical performance of the lithium-ion hybrid capacitor was achieved by optimizing the mass ratio of active materials between the Co-NTTA MOFs negative electrode and the activated carbon positive electrode to 1:12. The total mass of Co-NTTA MOFs and activated carbon was controlled at 15 mg / cm -2 .

[0060] Example 4

[0061] S1: Add triphenylamine triamide-derived hexacarboxylic acid (17 mg, 0.02 mmol) organic ligand, metal salt Co(NO3)2·6H2O (29.1 mg, 0.1 mmol), N,N-diethylformamide (DMF, 2 mL) and ethanol (1 mL) into a 25 mL reactor, seal it and place it in a 100 °C constant temperature oven for three days; after the reaction is completed, cool it to room temperature to finally obtain light purple cubic block crystals Co-NTTA MOFs.

[0062] The Co-NTTA MOFs, carbon nanotubes and acrylonitrile copolymer dispersion obtained in S1 were mixed evenly in a mass ratio of 8:1:1, and a solvent was added. The mixture was stirred for 30 min using a THINKY degassing machine to prepare a slurry. The obtained black viscous slurry was evenly scraped onto one side of the copper foil current collector and dried at a constant temperature of 120 °C for 12 h under vacuum conditions. A circular electrode with a diameter of 11 mm was punched out using a cutting machine. The active mass of a single lithium-ion battery negative electrode was 1.9 mg cm -2, a cobalt-based metal organic framework anode was obtained; a lithium sheet was used as a reference electrode and a counter electrode, a Celgard 2400 membrane was used as a separator, and a 1M lithium perchlorate-ethylene carbonate / diethyl carbonate (1:1, volume ratio) electrolyte was used. The prepared Co-NTTA MOFs electrode sheet was used as a cathode to assemble a Co-NTTA MOF||Li lithium-ion battery.

[0063] To reduce polarization and improve coulombic efficiency, Co-NTTA MOFs anode was used in lithium-ion batteries at 50 mA g -1 The current density was pre-cycled until the coulombic efficiency exceeded 95%. Then, the battery was discharged to 0.01 V (vs. Li / Li + ) and then assemble the full battery. Pre-lithiated Co-NTTA MOFs were used as the negative electrode and activated carbon as the positive electrode to construct a lithium-ion hybrid capacitor. Activated carbon, conductive carbon black and binder were mixed evenly in a mass ratio of 7:2:1, a solvent was added, and stirred in a THINKY degassing machine for 30 minutes to make a slurry. The resulting black viscous slurry was evenly scraped on one side of the aluminum foil current collector and dried at a constant temperature of 120°C under vacuum conditions for 12 hours. The optimal electrochemical performance of the lithium-ion hybrid capacitor was achieved by optimizing the mass ratio of active materials between the Co-NTTA MOFs negative electrode and the activated carbon positive electrode to 1:12. The total mass of Co-NTTA MOFs and activated carbon was controlled at 14 mg / cm -2

[0064] Example 5

[0065] S1: Add triphenylamine triamide-derived hexacarboxylic acid (17 mg, 0.02 mmol) organic ligand, metal salt Co(NO3)2·6H2O (29.1 mg, 0.1 mmol), N,N-diethylformamide (DMF, 6 mL) and ethanol (3 mL) into a 25 mL reactor, seal it and place it in a 100 °C constant temperature oven for three days; after the reaction is completed, cool it to room temperature to finally obtain light purple cubic block crystals Co-NTTA MOFs.

[0066] The Co-NTTA MOFs, carbon nanotubes and acrylonitrile multipolymer dispersion obtained in S1 were mixed evenly in a mass ratio of 8:1:1, deionized water solvent was added, and the mixture was stirred for 30 min using a THINKY degassing machine to prepare a slurry. The obtained black viscous slurry was evenly scraped onto one side of the copper foil current collector and dried at a constant temperature of 120 °C for 12 h under vacuum conditions. A circular electrode with a diameter of 11 mm was punched out using a cutting machine. The active mass of a single lithium-ion battery negative electrode was 1.6 mg cm -2, a cobalt-based metal organic framework anode was obtained; a lithium sheet was used as a reference electrode and a counter electrode, a Celgard 2400 membrane was used as a separator, and a 1M lithium perchlorate-ethylene carbonate / diethyl carbonate (1:1, volume ratio) electrolyte was used. The prepared Co-NTTA MOFs electrode sheet was used as a cathode to assemble a Co-NTTA MOF||Li lithium-ion battery.

[0067] To reduce polarization and improve coulombic efficiency, Co-NTTA MOFs anode was used in lithium-ion batteries at 50 mA g -1 The current density was pre-cycled until the coulombic efficiency exceeded 95%. Then, the battery was discharged to 0.01 V (vs. Li / Li + ) and then assemble the full battery. Pre-lithiated Co-NTTA MOFs were used as the negative electrode and activated carbon as the positive electrode to construct a lithium-ion hybrid capacitor. Activated carbon, conductive carbon black and binder were mixed evenly in a mass ratio of 7:2:1, a solvent was added, and stirred in a THINKY degassing machine for 30 minutes to make a slurry. The resulting black viscous slurry was evenly scraped on one side of the aluminum foil current collector and dried at a constant temperature of 120°C under vacuum conditions for 12 hours. The optimal electrochemical performance of the lithium-ion hybrid capacitor was achieved by optimizing the mass ratio of active materials between the Co-NTTA MOFs negative electrode and the activated carbon positive electrode to 1:12. The total mass of Co-NTTA MOFs and activated carbon was controlled at 13 mg / cm -2 .

[0068] Example 6

[0069] S1; Add triphenylamine triamide-derived hexacarboxylic acid (17 mg, 0.02 mmol) organic ligand, metal salt Co(NO3)2·6H2O (29.1 mg, 0.1 mmol), N,N-diethylformamide (DMF, 3 mL) and ethanol (2 mL) into a 25 mL reactor, seal it and place it in a 100 °C constant temperature oven for three days; after the reaction is completed, cool it to room temperature to finally obtain light purple cubic block crystals Co-NTTA MOFs.

[0070] The Co-NTTA MOFs, carbon nanotubes and acrylonitrile multipolymer dispersion obtained in S1 were mixed evenly in a mass ratio of 5:4:1, deionized water solvent was added, and the mixture was stirred for 30 min using a THINKY degassing machine to prepare a slurry. The obtained black viscous slurry was evenly scraped onto one side of the copper foil current collector and dried at a constant temperature of 120 °C for 12 h under vacuum conditions. A circular electrode with a diameter of 11 mm was punched out using a cutting machine. The active mass of a single lithium-ion battery negative electrode was 1.5 mg cm -2, a cobalt-based metal organic framework anode was obtained; a lithium sheet was used as a reference electrode and a counter electrode, a Celgard 2400 membrane was used as a separator, and a 1M lithium perchlorate-ethylene carbonate / diethyl carbonate (1:1, volume ratio) electrolyte was used. The prepared Co-NTTA MOFs electrode sheet was used as a cathode to assemble a Co-NTTAMOF||Li lithium-ion battery.

[0071] To reduce polarization and improve coulombic efficiency, Co-NTTA MOFs anode was used in lithium-ion batteries at 50 mA g -1 The current density was pre-cycled until the coulombic efficiency exceeded 95%. Then, the battery was discharged to 0.01 V (vs. Li / Li + ) and then assemble the full battery. Pre-lithiated Co-NTTA MOFs were used as the negative electrode and activated carbon as the positive electrode to construct a lithium-ion hybrid capacitor. Activated carbon, conductive carbon black and binder were mixed evenly in a mass ratio of 7:2:1, a solvent was added, and stirred in a THINKY degassing machine for 30 minutes to make a slurry. The resulting black viscous slurry was evenly scraped on one side of the aluminum foil current collector and dried at a constant temperature of 120°C under vacuum conditions for 12 hours. The optimal electrochemical performance of the lithium-ion hybrid capacitor was achieved by optimizing the mass ratio of active materials between the Co-NTTA MOFs negative electrode and the activated carbon positive electrode to 1:12. The total mass of Co-NTTA MOFs and activated carbon was controlled at 15 mg / cm -2 .

[0072] Example 7

[0073] S1: Add triphenylamine triamide-derived hexacarboxylic acid (17 mg, 0.02 mmol) organic ligand, metal salt Co(NO3)2·6H2O (29.1 mg, 0.1 mmol), N,N-diethylformamide (DMF, 5 mL) and ethanol (3 mL) into a 25 mL reactor, seal it and place it in a 100 °C constant temperature oven for three days; after the reaction is completed, cool it to room temperature to finally obtain light purple cubic block crystals Co-NTTA MOFs.

[0074] The Co-NTTA MOFs, carbon nanotubes and acrylonitrile multipolymer dispersion obtained in S1 were mixed evenly in a mass ratio of 5:4:1, deionized water solvent was added, and the mixture was stirred for 30 min using a THINKY degassing machine to prepare a slurry. The obtained black viscous slurry was evenly scraped onto one side of the copper foil current collector and dried at a constant temperature of 120 °C for 12 h under vacuum conditions. A circular electrode with a diameter of 11 mm was punched out using a cutting machine. The active mass of a single lithium-ion battery negative electrode was 1.7 mg cm -2, a cobalt-based metal organic framework anode was obtained; a lithium sheet was used as a reference electrode and a counter electrode, a Celgard 2400 membrane was used as a separator, and a 1M lithium perchlorate-ethylene carbonate / diethyl carbonate (1:1, volume ratio) electrolyte was used. The prepared Co-NTTA MOFs electrode sheet was used as a cathode to assemble a Co-NTTA MOF||Li lithium-ion battery.

[0075] To reduce polarization and improve coulombic efficiency, Co-NTTA MOFs anode was used in lithium-ion batteries at 50 mA g -1 The current density was pre-cycled until the coulombic efficiency exceeded 95%. Then, the battery was discharged to 0.01 V (vs. Li / Li + ) and then assemble the full battery. Pre-lithiated Co-NTTA MOFs were used as the negative electrode and activated carbon as the positive electrode to construct a lithium-ion hybrid capacitor. Activated carbon, conductive carbon black and binder were mixed evenly in a mass ratio of 7:2:1, a solvent was added, and stirred in a THINKY degassing machine for 30 minutes to make a slurry. The resulting black viscous slurry was evenly scraped on one side of the aluminum foil current collector and dried at a constant temperature of 120°C for 12 hours under vacuum conditions. The optimal electrochemical performance of the lithium-ion hybrid capacitor was achieved by optimizing the mass ratio of active materials between the Co-NTTAMOFs negative electrode and the activated carbon positive electrode to 1:12. The total mass of Co-NTTAMOFs and activated carbon was controlled at 16 mg / cm -2 .

[0076] It can be seen from the above examples that the high specific energy-rate cobalt-based metal organic framework anode material prepared in the examples of the present invention benefits from the rich lithium storage sites (-OC=O, -NH-C=O, active -C=C functional groups and cobalt cations), excellent structural stability, π-aromatic conjugated network and π...π stacked sp 2 Hybrid carbon, assembled Co-NTTA MOF||Li lithium-ion battery exhibits high specific capacity (956 mAh g -1 , 200mAg -1 ) and excellent rate performance (483mAhg -1 , 600 th , 5Ag -1 ). Based on the Faraday redox reaction and fast intercalation pseudocapacitive lithium storage behavior of Co-NTTA MOFs, a 4.3V high-performance lithium-ion hybrid capacitor was successfully constructed. The present invention provides a guarantee for the cycle stability and rate performance of negative electrode materials, and also provides a new research idea for the development of advanced organic framework materials for electrochemical energy storage technology.

[0077] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and playing the same role within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the subject matter of the present application, various deformations, modifications, substitutions, simplifications that can be thought of by those skilled in the art are applied to the embodiments, and other methods constructed by combining some of the constituent elements in the embodiments are also included in the protection scope of the present invention, and the protection scope of the present invention shall be subject to the claims.

Claims

1. A method for preparing a high specific energy-rate cobalt-based metal organic framework negative electrode material, characterized in that: The following steps are involved: S1: The triphenylamine triamide-derived hexacarboxylic acid organic ligand, Co(NO3)2·6H2O, N,N-diethylformamide and ethanol were mixed and added into a reactor, which was sealed and placed in a constant temperature oven for reaction. After the reaction was completed, the mixture was cooled to room temperature to obtain Co-NTTAMOFs.

2. The method for preparing a high specific energy-rate type cobalt-based metal organic framework negative electrode material according to claim 1, characterized in that: The reaction time described in S1 is 3 days and the reaction vessel is 25 mL.

3. The method for preparing a high specific energy-rate type cobalt-based metal organic framework negative electrode material according to claim 1, characterized in that: The molar ratio of the triphenylamine triamide-derived hexacarboxylic acid organic ligand and Co(NO3)2·6H2O described in S1 is 1:

5.

4. The method for preparing a high specific energy-rate type cobalt-based metal organic framework negative electrode material according to claim 1, characterized in that: The volume ratio of N,N-diethylformamide to ethanol described in S1 is 2-6:1-3.

5. A high specific energy-rate type cobalt-based metal organic framework negative electrode material obtained by the preparation method according to any one of claims 1 to 4, characterized in that: The negative electrode material is a sp with abundant lithium storage sites, excellent structural stability, π-aromatic conjugated network and π...π stacking. 2 Hybridized carbon structure.

6. Use of a high specific energy-rate cobalt-based metal organic framework negative electrode material according to claim 5, wherein the cobalt-based metal organic framework negative electrode material is used in assembling lithium ion batteries and lithium ion hybrid capacitors.

Citation Information

Patent Citations

  • Preparation method and application of triphenylamino metal organic framework compound capable of catalyzing carbon dioxide-epoxy compound cycloaddition

    CN106423282A

  • Application of cobalt-base metallic organic frame material

    CN106935862A